Characteristics of metabolic acidosis and management of rotavirus gastro-enteritis - Dhelaria, Anshoo; Commondoor, Raghuram; Kar, Ananya; Eisenhut, Michael (Journal of Pediatric Biochemistry, 2010)
Objectives of this study were to investigate the characteristics of metabolic acidosis associated with rotavirus gastroenteritis and to explore them as a tool in the management of dehydration. The study was retrospective, case record based and conducted in a secondary level District General Hospital. Included study population were 133 children who were admitted to the Paediatric Unit with rotavirus gastroenteritis. Degree of dehydration, result of blood gas analysis, C-reactive protein level, urinary ketones, renal function tests, fluid management and duration of hospitalization were recorded and results compared between patients with and without severe metabolic acidosis (serum bicarbonate < 17 mmol/L). Out of 133 patients, blood gas analysis was obtained in 78 (59%) and 73 (94%) of those showed metabolic acidosis (bicarbonate < 22 mmol/L). Thirty five patients developed severe metabolic acidosis. Patients with severe metabolic acidosis showed signs of dehydration more commonly (97% vs. 74%, p < 0.05) and required intravenous rehydration more frequently (94% vs. 63%, p < 0.05) than those who were not severely acidotic. With respect to gender ratio, initial temperature, serum levels of C-reactive protein, chloride, anion-gap, lactate and ketonuria, there were no significant differences between the severely acidotic patients and those who were not. Urea and creatinine levels were higher (46.6 (11.7) versus 37.8 (11.9) micromole/L for creatinine and 5.5 (1.9) versus 4.2 (2.1) mmol/L for urea, p < 0.05) in patients with severe metabolic acidosis and correlated significantly negatively (for both: r = − 0.29, p = 0.02) with serum bicarbonate levels. We concluded that the majority of children attending hospital with rotavirus gastroenteritis had a metabolic acidosis. Severe metabolic acidosis was associated with more severe dehydration and higher urea and creatinine levels and increased requirement for intravenous fluid boluses and intravenous rehydration. A bicarbonate level of > 17 mmol/L excluded severe clinical dehydration and below this level a degree of dehydration was very likely.
Keywords: Metabolic acidosis; rotavirus; dehydration; gastroenteritis